Ketogenic diet ameliorates cognitive impairment and neuroinflammation in a mouse model of Alzheimer’s disease - Xu, Yunlong; Jiang, Chenyu; Wu, Junyan; Liu, Peidong; Deng, Xiaofei; Zhang, Yadong; Peng, Bo; Zhu, Yingjie (CNS neuroscience & therapeutics, 2022)
Introduction Alzheimer's disease (AD) is the most common neurodegenerative disorder that causes dementia and affects millions of people worldwide. Although it has devastating outcomes for patients and tremendous economic costs to society, there is currently no effective treatment available. Aims The high‐fat, low‐carbohydrate ketogenic diet (KD) is an established treatment for refractory epilepsy with a proven efficacy. Although the considerable interest has emerged in recent years for applying KD in AD patients, only few interventional studies in animals and humans have addressed the effects of KD on cognitive impairments, and the results were inconclusive. The aim of this study was to explore the impact of KD on cognitive functions and AD pathology in 5XFAD mice—a validated animal model of AD. Results Four months of a ketogenic diet improved spatial learning, spatial memory and working memory in 5XFAD mice. The improvement in cognitive functions was associated with a restored number of neurons and synapses in both the hippocampus and the cortex. Ketogenic diet treatment also reduced amyloid plaque deposition and microglial activation, resulting in reduced neuroinflammation. The positive effect of ketogenic diet on cognitive functions depended on the starting time and the duration of the diet. A shorter period (2 months) of ketogenic diet treatment had a weaker effect. Ketogenic diet initiated at late stage of AD (9 months of age) displayed no effect on cognitive improvement. Conclusions These findings indicate positive effects of ketogenic diet on both cognitive function and histopathology in Alzheimer's disease, which could be due to reduced microglial activation and neuroinflammation. Our findings provide new insights and therapeutic interventions for the treatment of Alzheimer's disease. Ketogenic diet improved cognitive functions, decreased amyloid plaque deposition and microglial activation, restored synaptic and neuronal density, and reduced neuroinflammation.